Kemampuan Berpikir Kritis Matematis Siswa SMP berdasarkan Watson Glaser Critical Thinking Appraisal - Dinar Nur Alkifah Jihadatunnafsy; Sufyani Prabawanto; Endang Cahya (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2025)
This research aims to examine and to describe mathematical critical thinking ability of Junior high school based on Watson-Glaser Critical Thinking Appraisal (WGCTA). This type of research is qualitative research with case study design. The study involved 19 students of class VIII at one of junior high school in West Bandung. The data obtained are the results of test and interview. The analysis techniques used include data reduction, data presentation, and research conclusion. Based on the data analysis and the finding of the research, it can be concluded that there are many students who have not fulfill the indicators of critical thinking, there are 12 students who fulfill assumption indicator, 14 students who fulfill interpretation indicator, 1 student who fulfill argument analysis indicator, and 12 students who fulfill make a conclusion. The students who cannot fulfill the indicators of critical thinking are caused by students forget how to solve the problem, do not understand about materials so students cannot solve the problem, cannot prove the truth, and cannot give a correct argument.